2018
DOI: 10.5433/1679-0359.2018v39n2p593
|View full text |Cite
|
Sign up to set email alerts
|

Short-term evaluation of an intra-articular technique for cranial cruciate ligament rupture in dogs using nylon or polyester

Abstract: Cranial cruciate ligament rupture (CCrLR) is a common condition found in the small animal routine, being correlated to traumas, obesity, genetic factors, and primary osteoarthritis (OA) in dogs. Affected animals show articular instability that, if not corrected surgically, may cause secondary OA and loss of limb function. The aim of this study was to compare short-term results of the intra-articular technique for knee stabilization after CCrLR using a surgical button associated with polyester yarn (Group A), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although, innovative materials with improved biocompatibility and excellent strength are available in the market (GOMIDE et al, 2019), several studies have reported on the use of intraarticular synthetic polyester implants to replace ruptured ligaments (ROOSTER et al, 2001;SELMI et al, 2002;PRZĄDKA et al, 2017;PRADA et al,2018), with a higher incidence of complications related to inefficient surgical technique than to material biocompatibility, according to PRADA et al (2018). The main advantages of braided multifilament surgical polyester thread include non-absorption and load capacity maintenance over time (MÜLLER et al, 2016); in contrast, due to its characteristics, it triggers moderate tissue reaction with a 3-week peak followed by reduction (ESENYEL et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Although, innovative materials with improved biocompatibility and excellent strength are available in the market (GOMIDE et al, 2019), several studies have reported on the use of intraarticular synthetic polyester implants to replace ruptured ligaments (ROOSTER et al, 2001;SELMI et al, 2002;PRZĄDKA et al, 2017;PRADA et al,2018), with a higher incidence of complications related to inefficient surgical technique than to material biocompatibility, according to PRADA et al (2018). The main advantages of braided multifilament surgical polyester thread include non-absorption and load capacity maintenance over time (MÜLLER et al, 2016); in contrast, due to its characteristics, it triggers moderate tissue reaction with a 3-week peak followed by reduction (ESENYEL et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Such implants can be implanted either (i) extra-articularly as in the FLO (1975) or the TightRope (TR) ( Cook et al , 2010 ) techniques; or (ii) intra-articularly as introduced recently by Barnhart et al (2016) and several other authors ( Cook et al , 2017 ; Prada et al , 2018 ) for synthetic implants, or by Biskup and Conzemius (2020) for intra-articular allografts. Unfortunately, in human anterior cruciate ligament (ACL) surgery, synthetic intra-articular techniques have failed several times in the last quarter of the 20th century ( Legnani et al , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to this recent trend, brand new intra-articular devices have been developed for passive stabilization of the stifle, composed of an ultrahigh molecular weight polyethylene (UHMWPE) artificial ligament fixed on the bones with interference screws ( Blanc et al , 2019 ; Goin et al , 2019 ; Rafael et al , 2020 ). This approach seems to be spreading among the international veterinary community ( Barnhart et al , 2016 ; Cook et al , 2017 ; Barnhart et al , 2018 ; Prada et al , 2018 ; Barnhart et al , 2019a; Biskup and Conzemius, 2020 ), although it remains marginal in the treatment of CCL rupture ( von Pfeil et al , 2018 ). The objective of this study is to evaluate the biomechanical behavior of this new artificial ligament implanted in ex vivo stifles under cyclic tensile tests.…”
Section: Introductionmentioning
confidence: 99%